Spatial modelling of shallow groundwater quality in coastal areas with Kriging interpolation - Arbi, Yaumal; Syah, Nurhasan; Umar, Iswandi; Dewata, Indang; Gusman, Mulya; Sandra, Nevy (Teknomekanik, 2026)
This study maps shallow coastal groundwater quality in Padang, Indonesia, using four operational parameters: potential of hydrogen (pH), electrical conductivity (EC), total dissolved solids (TDS), and salinity. We characterize spatial dependence using empirical variograms, evaluate directional anisotropy, and generate prediction surfaces with Ordinary Kriging. The variogram analysis indicates stronger spatial continuity along the coastline for EC and TDS, while salinity shows shorter continuity with a distinct directional structure, reflecting localized freshwater-seawater mixing processes. Groundwater pH remains neutral to slightly alkaline and exhibits lower spatial variability than EC, TDS, and salinity. Leave-one-out cross-validation supports the reliability of the kriging estimates at the study scale, indicating low prediction error and strong agreement between observed and predicted values. The resulting thematic maps enable a three-level quality zoning that differentiates a lower-risk northern segment, a transitional central belt, and a higher-risk southern segment consistent with seawater intrusion influence. These outputs provide a practical basis for prioritizing monitoring locations, protecting vulnerable wells, and strengthening evidence-based coastal groundwater management aligned with SDG 6 Clean Water and Sanitation and SDG 11 Sustainable Cities and Communities.